PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GIKEN PRECISION INDONESIA - Damanik, Sofia Laura; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2021)
Economic globalization requires the business world as one of the economic actors to improve in the face of increasingly fierce competition. In order to compete in order to maintain the existence of the business, the company must be able to utilize its resources in order to achieve results effectively and efficiently. That studies aims are determining the effected of work motivation and work discipline on employee performance at PT Giken Precision Indonesia. Data collection techniques by distributing questionnaires to 111 employes of PT Giken Precision Indonesia. The results of this studies indicated that work motivation (X1), work discipline (X2) partially and simultaneously significant effect on employee performance (Y). The results of the coefficient of determining testing showed that work motivation (X1), work discipline (X2) affect employee performance (Y) by 87.6 percent, while the remaining 12.4 percent is influenced by other variables not examined in this study. Keywords: Employee Performance; Work Discipline; and Work Motivation.